An extension of the Pólya-Szegö operator inequality - Hoa, Dinh Trung (2017)
We extend an operator Pólya-Szegö type inequality involving the operator geometric mean to any arbitrary operator mean under some mild conditions. Utilizing the Mond-Pečarić method, we present some other related operator inequalities as well.